Nomination skills of pre-school children - Kij, Monika (Logopedia Silesiana, 2020)
This paper aims to investigate the level of naming skills of children between four and six years of age and to check if pre-schoolers, while naming new toys on the ad-hoc basis, do it randomly or whether the process is systemic. The methods, as well as the elements of extra-linguistic reality, used in the creation of names by children are analyzed. Moreover, efforts were made to deepen the study by analysing the influence of socio-cultural factors such as age and gender on nomination skills of children.